2023
DOI: 10.1093/nar/gkac1237
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of the RNA-binding protein PURA triggers changes in posttranscriptional gene regulation and loss of P-bodies

Abstract: The RNA-binding protein PURA has been implicated in the rare, monogenetic, neurodevelopmental disorder PURA Syndrome. PURA binds both DNA and RNA and has been associated with various cellular functions. Only little is known about its main cellular roles and the molecular pathways affected upon PURA depletion. Here, we show that PURA is predominantly located in the cytoplasm, where it binds to thousands of mRNAs. Many of these transcripts change abundance in response to PURA depletion. The encoded proteins sugg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 82 publications
5
17
0
Order By: Relevance
“…Consistent with previous reports (Daigle et al, 2016;Markmiller et al, 2018), we observed that hsPURA co-localizes to stress granules in Very recently, hsPURA was reported to localize to P-bodies (Molitor et al, 2023). In a recent study, it was shown that a hsPURA knock-down in HeLa and in fibroblast cells resulted in down-regulation of the essential P-body proteins LSM14a and DDX6 and, most likely as a direct consequence, in strongly impaired P-body formation (Molitor et al, 2023). In light of this report, our finding that patient-derived mutations impair the P-body association of hsPURA (Fig…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with previous reports (Daigle et al, 2016;Markmiller et al, 2018), we observed that hsPURA co-localizes to stress granules in Very recently, hsPURA was reported to localize to P-bodies (Molitor et al, 2023). In a recent study, it was shown that a hsPURA knock-down in HeLa and in fibroblast cells resulted in down-regulation of the essential P-body proteins LSM14a and DDX6 and, most likely as a direct consequence, in strongly impaired P-body formation (Molitor et al, 2023). In light of this report, our finding that patient-derived mutations impair the P-body association of hsPURA (Fig…”
Section: Discussionsupporting
confidence: 93%
“…In order to assess the localization of hs PURA to cytoplasmic granules in unstressed conditions, we first recapitulated its recently reported localization to P-bodies (Molitor et al , 2023). Co-staining with the marker DCP1A indeed confirmed a co-localization of overexpressed hs PURA in P-bodies of HeLa cells ( Fig 2A and 2B ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations